Herbicide free agriculture? A bio-economic modelling application to Swiss wheat production. (July 2019) - Böcker, Thomas; Möhring, Niklas; Finger, Robert
Abstract: Herbicide application in agricultural systems is currently critically discussed because of its possible adverse effects on the environment and human health. Currently, governments and food industry actors search for solutions to reduce herbicide use on farms. Yet, potential consequences of herbicide reductions on a farm-level are not well known. The goal of this article is to develop and apply a bio-economic modelling approach to simulate how farmers and agricultural systems react to a potential ban of glyphosate and eventually of all herbicides. We apply this approach for Swiss Extenso wheat production, which is a widespread form of wheat production in Switzerland, where pesticide use is currently limited to herbicides and seed treatments. Our modelling approach combines spatially explicit, detailed information on weed pressure, possible yield effects of weeds and efficacy and costs of 140 weed control strategies in a spatially explicit economic decision model. We assess the strategies optimal for farmers in response to i) glyphosate-free and ii) herbicide-free production requirements in terms of economic losses, yield reductions and environmental impacts. We find economic losses in the glyphosate-free production scenario of up to CHF 119/ha and in the herbicide-free scenario of up to CHF 192/ha, with respective yield reductions ranging between 0.8 and 2.7 dt/ha (i.e. of up to 6%). However, possible economic losses would be outweighed by existing Swiss agri-environmental direct payments for herbicide-free and reduced tillage production systems. We find that restrictions with respect to glyphosate and herbicide use imply trade-offs between the reduction in pesticide risks for the environment and human health versus higher energy consumption. Yet, these trade-offs can be limited if incentive schemes for glyphosate and herbicide reduction are combined with requirements to prevent more intensive tillage. Highlights: We develop and apply a bio-economic modelling approach to simulate farmers weed control. We analyze effects of a potential ban of glyphosate and eventually of all herbicides in Swiss Extenso wheat production. The removal of glyphosate and all herbicides reflects current discussions in Swiss wheat value chains. We quantify economic and environmental consequences arising from bans of glyphosate and all herbicides. We find moderate economic losses and moderate yield reductions arising from bans of glyphosate and all herbicides. Possible economic losses would be outweighed by existing Swiss agri-environmental direct payments. We find significant reductions of risks for the environment and human health due to pesticide use if glyphosate (and all herbicides) are removed. Effects on the energy balance of wheat production are ambiguous.